Western gorilla space use suggests territoriality - Morrison, Robin E. (Sci Rep, 2020)
The evolutionary origins of how modern humans share and use space are often modelled on the territorial-based violence of chimpanzees, with limited comparison to other apes. Gorillas are widely assumed to be non-territorial due to their large home ranges, extensive range overlap, and limited inter-group aggression. Using large-scale camera trapping, we monitored western gorillas in Republic of Congo across 60 km(2). Avoidance patterns between groups were consistent with an understanding of the “ownership” of specific regions, with greater avoidance of their neighbours the closer they were to their neighbours’ home range centres. Groups also avoided larger groups’ home ranges to a greater extent, consistent with stronger defensive responses from more dominant groups. Our results suggest that groups may show territoriality, defending core regions of their home ranges against neighbours, and mirror patterns common across human evolution, with core areas of resident dominance and larger zones of mutual tolerance. This implies western gorillas may be a key system for understanding how humans have evolved the capacity for extreme territorial-based violence and warfare, whilst also engaging in the strong affiliative inter-group relationships necessary for large-scale cooperation.